The Impact of Material Flow Cost Accounting on Resource Efficiency in Small-Scale Soybean Oil Production - Joel, Ayotola; Doorasamy, Mishelle; Akinola, Wilfred (Journal of Business Management and Accounting, 2025)
This study adopted the case study approach to examine material flow cost accounting (MFCA) as a measure of resource efficiency and environmental sustainability in small-scale soybean oil production in South Africa. Data were gathered primarily through direct observation of the soybean oil production process over three months. To achieve the study’s first objective, the Pareto chart was employed to determine and analyse the leading root cause of the negative product cost. The result of the MFCA and Pareto chart analysis found that the highest negative material cost was incurred during the oil extraction process. Therefore, the improvement plan was concentrated on reducing the negative material cost. An investigation into the root cause of these high negative costs was then carried out to seek improvement, after which improvement methods were proposed and implemented. Descriptive statistics and Microsoft Excel were employed to analyse the results obtained before and after the improvement plan implementation. The study found that applying the MFCA technique resulted in a reduction in the negative material costs from 1648.4 Rands to 1359.15 Rands; system costs reduced from 791.69Rands to 622.65 Rands; waste costs reduced from 270 Rands to 249.50 Rands, while energy cost that was expected to increase actually had a reduction from 118.94 Rands to 93.51 Rands. This study, therefore, recommends the application of the MFCA technique in small-scale soybean oil production and similar production processes.
Keywords: material flow cost accounting; cost reduction; soybean oil; waste reduction; pareto chart